The Construction of the Meaning of al-aql and al-qalb in Tafsir Mafatih al-Ghaib - Ahmad Humaidi; Dian Erwanto (CV. Doki Course and Training, 2025)
This study examines the role of reason (al-aql) and heart (al-qalb) in the Qur'an as cognitive and spiritual tools for humans. QS. al-Ankabut: 43 emphasizes the importance of reason in understanding divine parables, while QS. al-A'raf: 179 highlights human negligence in not using the heart to grasp the meaning of Allah's verses. The method used is analytical interpretation, through the perspective of Tafsir Mafatih al-Ghaib by Fakhruddin Al-Razi, which is known for its rational and philosophical approach. This study concludes that in Al-Razi's interpretation, reason is understood as an intellectual ability that enables scholars (al-'alimun) to interpret the parables of the Qur'an in depth through the process of ta'aqqul, which is holistic thinking that integrates rational analysis with revelatory guidance. Reason plays a role in assessing truth in the aspects of belief, law, and ethics. Meanwhile, the heart is the center of spiritual awareness (lathīfah rūḥiyyah), which enables humans to experience a spiritual journey (suluk), attain knowledge of Allah (wushul), and purify the soul from diseases of the heart (tazkiyah). Failure to use the heart causes humans to go astray, even becoming lower than other creatures. The findings of this study show that reason and the heart complement each other. Reason functions as a tool for rational analysis, while the heart is the center of internalization of spiritual values. An imbalance between the two, for example, relying on reason without purifying the heart, has the potential to produce a superficial understanding. The implications of this research are important for Islamic education, namely the integration of cognitive and spiritual development in the curriculum, as well as for contemporary life, by emphasizing the balance between reason and heart in facing modern challenges such as spiritual crises and the spread of disinformation.